2002
DOI: 10.1093/ps/81.3.321
|View full text |Cite
|
Sign up to set email alerts
|

Fearfulness and Performance Related Traits in Selected Lines of Japanese Quail (Coturnix japonica)

Abstract: Fearfulness and economic traits were studied in three lines of Japanese quail. Two of the lines were of the same genetic origin and were subjected to divergent selection for the duration of tonic immobility (TI), a measure of fearfulness. Birds were selected for long (LTI) or short (STI) duration of TI. The third line (DD) was of a different genetic origin and had been selected for early egg production. Fear, growth, residual feed intake, and measures of egg composition and production varied among lines. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 15 publications
1
15
1
7
Order By: Relevance
“…Esse resultado é similar ao relatado por Altan et al (1998), que não encontraram diferenças significativas para produção de ovos de linhagens selecionadas para alto ganho de peso. Outros autores reportaram resultados contrários aos deste estudo (Minvielle et al, 2002;Piccinin, 2002;Anthony et al, 1990;Marks, 1979), pois obtiveram diferenças significativas para produção de ovos entre linhagens. As diferenças entre estes resultados e os obtidos na literatura podem ser explicadas pela variabilidade genética entre as aves utilizadas nas diferentes investigações.…”
Section: Resultsunclassified
“…Esse resultado é similar ao relatado por Altan et al (1998), que não encontraram diferenças significativas para produção de ovos de linhagens selecionadas para alto ganho de peso. Outros autores reportaram resultados contrários aos deste estudo (Minvielle et al, 2002;Piccinin, 2002;Anthony et al, 1990;Marks, 1979), pois obtiveram diferenças significativas para produção de ovos entre linhagens. As diferenças entre estes resultados e os obtidos na literatura podem ser explicadas pela variabilidade genética entre as aves utilizadas nas diferentes investigações.…”
Section: Resultsunclassified
“…Muir and Craig, 1998). Hence, genetic lines of poultry have been created in order to decrease feather pecking or fear, or to increase social motivation (Minvielle et al, 2002). Previous studies evidenced that chronic stress had fewer effects on the fearfulness and hypothalamic-pituitary-adrenal (HPA) axis response of quail selected for their low level of fearfulness than on that of quail selected for their high level of reactivity (Calandreau et al, 2011;Laurence et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Schü tz et al, 2004). In quail, Minvielle et al (2002) observed the absence of genetic correlation between tonic immobility and production traits, which contradicts the hypothesis that fear and production are related. Similarly, the QTL found for the duration of tonic immobility did not co-locate with the QTL for growth and feed intake Minvielle et al, 2005).…”
Section: Maternal Behaviourmentioning
confidence: 78%
“…Montanholi et al (2010) observed that high-RFI steers make more visits to the feeder during the night than more efficient steers. Altan et al (2004) found that low-RFI quail were less fearful, whereas Minvielle et al (2002) did not find any significant correlation between RFI and the results of the tonic immobility test. In laying hens selected for lower RFI, reduced sensitivity to stress is observed under natural conditions (Schü tz et al 2002), but these genotypes are selected in cages.…”
Section: Genetics Of the Behavioural Response To Changes In The Physimentioning
confidence: 95%
See 1 more Smart Citation